Of Time, Intelligence, and Institutions. - Browder, Felix E. (Daedalus: Journal of the American Academy of Arts & Sciences)
Presents an argument which says the future achievement of the United States in science and technology must, in a large part, derive from American universities and the talented young people they educate in order for massive parallel processing to be realized. Suggestion that parallel processing must be interwoven with the main thrust of scientific and engineering research in the universities; Reference to the deep involvement of time and intelligence in the computer; More.